EVALUASI SISTEM PENGENDALIAN INTERN TERHADAP PEMBERIAN KREDIT BUMDES BANGUN BERSAMA - Nurhadi Kamaluddin; Melly Asih Haryati (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
The purpose of this research is to know about the credit giving system and the implementation of internal control system of credit giving in BUMDes Bangun Bersama Kepunduhan village. The data that used in this research is qualitative data.and the analytical method is depcriptive qualitative method. The result showed that the credit giving system in BUMDes Bangun Bersama Kepunduhan village is consist of 5 procedures that is credit request, credit analysis, decision awarding, credit dibursement and repayment of credit. The implementation of internal control system of credit giving in BUMDes Bangun Bersama are based on 5 elements of internal control system. Based on the result of the quesstionnaire it can be concluded that the internal control system of credit giving of BUMDes Bangun Bersama Kepunduhan village Kramat sub-district Tegal district is exactly effective.Keywords : Internal Control System, Credit, BUMDes